LADDER STRUCTURE BOX TYPE DESIGN FOR BUCKET LINE DREDGER - NUGRAHA (NIM : 13107013); Pembimbing : Rachman Setiawan, S.T., M.Sc., Ph.D., GILANG
A bucket line dredger is a type of ship that is used to dredge material from the seabed using bucket chain. The dredger is designed to operate at off coast with maximum dredging depth of 50 meters. One of the main components of the dredger is ladder. Ladder receiving load from bucket weight, another component weight, its own weight, and load from dredging process. Ladder existing is a lattice structure which has mass large enough and has small relative stiffness. Ladder dredger should have the properties of light, stiff, strong, and safe. With the advancement welding technology and the increasingly use of plate, in this final assignment, it is proposed to use box type rather than lattice type. The design of this box ladder type based on several cases of loading, i.e. the slope of the ladder (10o, 45o, 50o, and 52o) and the variation number of buckets (167 buckets, 168 buckets, and 170 buckets). The analysis performed to determine the strength and deflection ladder structure that has been designed for operating conditions that have been determined. The design also considers the number of bucket to dredge and minimum catenary force. Based on the optimum design, the maximum stress is found to be 77 MPa with safety factor of 3 for the case of maintenance with slope of the ladder is 10o. The maximum deflection is 84 mm for the case of dredging with slope of the ladder is 45o. Both result satisfy the design criteria. The mass of the new ladder box design is 610 tons. By assuming an additional mass of the welded joints and other of 10% of the mass of the model, the total mass of the ladder is 671 tons, which is lower than the mass of ladder lattice model (900 tons).